Electroless Plating on Polymer Surfaces: Comprehensive Review of Mechanism, Process, Analysis, and Future Applications - Na Kyoung Kim; Seung Min Kang; Taegyun Kim; Suhyeon Kim; Geon Hwee Kim (Advanced Materials Interfaces)
Abstract Electroless plating is a solution‐based metal deposition technique through redox reaction, without external power. Due to its simple, versatile, and low‐cost process, coupled with high compatibility with various metals, electroless plating has become a key technology in many industrial fields such as electronics, automotive, aerospace, and biomedical engineering. Recent advances in electroless plating have enabled sophisticated plating on polymers and three‐dimensional surfaces, making it a prominent technology in emerging fields such as selective laser sintering, additive manufacturing, and wearable technology. This review provides a comprehensive overview of electroless plating, from its core theory to the latest research trends. Initially, the detailed mechanism of electroless plating is described, followed by an examination of the plating process. Then, the compositions of a typical electroless plating bath are introduced, and the critical operating parameters are categorized. Next, the evaluation factors of electroless plated surfaces are discussed, along with the current limitations of electroless plating technology. Finally, the various applications of electroless plating studied to date are presented, and future directions for this technology are suggested.